Design and development of sequential algorithm (SeQ) code for OCDMA system - Siti Fazlina Che 'Ad author (School of Computer and Communication Engineering, 2018)
The main goal of this research is to develop a new class of OCDMA encoder / decoder which can be improved the performance of OCDMA communication system. The objectives of this research are to formulate a new algorithm for PIIN and MAI cancellation properties by using SeQ code; to design a new encoder / decoder based SeQ code on purposed new algorithm with various cross correlation; to validate this new proposed code between theoretical and simulation.